The Magical and Charming Chinese Language Helping Chinese Tourism Market with a New Look & a New Height in Bali - Tao Xian Guang (International Journal of Interreligious and Intercultural Studies, 2022)
China is an ancient civilization with a splendid culture of 5,000 years. It has a long history and a broad and profound culture. The Chinese language is magical and unique with a long history and a profound background. It is unique among many languages in the world and with the largest number of people in the world. The UN World Tourism Organization has recently officially designated Chinese as an official language. In the era of globalization, the importance of internationalization of Chinese is self-evident. Currently, the Tourism Confucius Institute established at Udayana University in Bali is an important platform for Chinese language promotion. Bali, as a world-class tourist destination, is the first choice for Chinese tourists to visit Indonesia. Among the tourists from all over the world, Chinese tourists occupied one third. It is the main force of tourism consumption in Bali and has a very special status. Carrying out Chinese (tourism) teaching here can improve the Chinese level and service quality of local tourism practitioners in receiving Chinese tourists and effectively communicate with Chinese tourists and provide high-quality services and ensure the sustainable development and virtuous circle of the Chinese tourist market in Bali. It also contributes to the friendly cooperation between China and Indonesia in tourism and other fields, and cultivate comprehensive tourism Chinese talents for the tourism development in Bali, meanwhile, after the pandemic, when Chinese tourists arrived as scheduled, it helps Bali's tourism development showing a new look and the tourism economy reaching a new height.